Predictors of physical activity among women in Bojnourd, north east of Iran: Pender's health promotion model - Seyedeh Belin Tavakoly Sany; Mohammad Vahedian Shahroodi; Zahra Hosseini Khaboshan; Arezoo Orooji; Habibollah Esmaeily; Alireza Jafari; Mohammad Tajfard (BMC, 2021)
Abstract Background This study examined how socio-demographic characteristics constructs derived from the health promotion model (HPM) influence the level of physical activity (PA) women in Bojnourd, North East of Iran. Method This cross-sectional study has been carried out through multi-stage sampling design on 356 women aged 18-60 years living in Iran. Data was collected through reliable and valid questionnaire survey women who were selected from their homes. Results Most of participants (53.40%) had a low level of physical activity behaviors with minimal physical activity (PA) scores. Using regression analysis showed that 23.22% of the total variance in PA behaviors was predicted by socio-demographic variables, whilst 40.81% of the variance in PA behaviors was predicted by constructs from the HPM. The results from Path modeling indicated that prior behavior, interpersonal influences, perceived self-efficacy, perceived barriers and commitment to PA, were significant predictors for PA behaviors with 86.93% of total effects on PA, whereas, activity-related affect and situational influences had no significant effect on the PA behaviors. Conclusions We found that constructs derived from the HPM are determinants of PA among Iranian women and may be important in developing educational intervention programs to facilitate a physically active lifestyle in this population.